The Effect of Discounts and Free Shipping on Impulsive Purchases Moderated by Seller Service - Winike Kushindrajati Aprilia; Novi Diah Wulandari; Aris Kusumo Diantoro (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
This research was conducted to determine the relationship between discounts, free shipping and impulse purchases moderated by the seller's service. The population in this study were all Generation-Z users of the Shopee marketplace in Yogyakarta using the Smart PLS 3 application. The research sample uses a non-probability sampling technique with purposive sampling method. This study shows a relationship between discounts and free shipping on impulse purchases. In addition, the seller's service is pure moderation between discounts, free shipping against impulse purchases. The reseacrh has limitations that it is to be on a discount, free shipping, seller service, impulse purchases and focus on a Generation-Z that’s avaliable in Yogyakarta. This study will give insight to readers especialy in the field of marketing about the impulsive buying behavior of Generation-Z in the Shopee marketplace with discounts and free shipping as the independent variables, as well as the involvement of seller services as a moderating variable. The difference in this research is to use the seller's service as a moderating variable to find out a deeper relationship between the independent and dependent variables. Using Generation-Z in Yogyakarta which has never been done by previous researchers.